2021
DOI: 10.1038/s41419-021-04257-8
|View full text |Cite
|
Sign up to set email alerts
|

ERK5 modulates IL-6 secretion and contributes to tumor-induced immune suppression

Abstract: Tumors exhibit a variety of strategies to dampen antitumor immune responses. With an aim to identify factors that are secreted from tumor cells, we performed an unbiased mass spectrometry-based secretome analysis in lung cancer cells. Interleukin-6 (IL-6) has been identified as a prominent factor secreted by tumor cells and cancer-associated fibroblasts isolated from cancer patients. Incubation of dendritic cell (DC) cultures with tumor cell supernatants inhibited the production of IL-12p70 in DCs but not the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 78 publications
0
14
0
1
Order By: Relevance
“…Moreover, ERK5 ablation in malignant mesothelioma cells is accompanied by a significant reduction in tumor size as a result of the downregulation of critical angiogenesis-related (IL-8, VEGF) and proinflammatory (RANTES/CCL5, MCP-1/CCL2) cytokines [ 81 ]. Furthermore, recent studies on LC cells identified ERK5 as a key regulator of IL-6 secretion, which in turn determined the production of IL-12p70 by dendritic cells (DCs) and impaired the differentiation of Th1 cells [ 164 ].…”
Section: Role Of Erk5 In Tumor Microenvironmentmentioning
confidence: 99%
“…Moreover, ERK5 ablation in malignant mesothelioma cells is accompanied by a significant reduction in tumor size as a result of the downregulation of critical angiogenesis-related (IL-8, VEGF) and proinflammatory (RANTES/CCL5, MCP-1/CCL2) cytokines [ 81 ]. Furthermore, recent studies on LC cells identified ERK5 as a key regulator of IL-6 secretion, which in turn determined the production of IL-12p70 by dendritic cells (DCs) and impaired the differentiation of Th1 cells [ 164 ].…”
Section: Role Of Erk5 In Tumor Microenvironmentmentioning
confidence: 99%
“…NF-κB signaling or the MAPK signaling pathway are typically responsible for controlling the production of in ammatory factors [31,32]. As a result, we were able to identify the protein levels and phosphorylation levels of the pathways major players, ERK1/2, p38, JNK, and p65.…”
Section: Discussionmentioning
confidence: 95%
“…В литературе также имеются противоречивые данные о том, что IL-6 в опухолевом микроокружении способствует как дифференцировке иммуносупрессивных опухоль-ассоциированных макрофагов, миелоидных супрессорных клеток [23,24], толерогенных ДК [25], так и дифференцировке, активации и пролиферации Т-лимфоцитов [24,26]. IL-10 описан как мощный иммуносупрессивный фактор, способствующий привлечению в опухоль Treg и подавлению NK-клеток [27,28], а также дифференцировке макрофагов в М2 [29,30] и приобретению ДК толерогенного фенотипа [25,31].…”
Section: Discussionunclassified